Economic Versus Political Liberalisation In Asean: Public Opinion Among University Students In Four Member Countries - Benny, Guido; Daud, Sity; Moorthy, Ravichandran (Penerbit Universiti Sains Malaysia (USM Press), 2018)
As a regionalism initiative, establishment of the ASEAN Community needs plausible level of public awareness, good public perception and strong public support from the public for its legitimacy. The current paper discusses the opinion among the public pertaining to regional economic integration under the ASEAN Economic Community initiative in comparison to political-security cooperation under the ASEAN Political Security Community in 2015 among educated public in four ASEAN countries, namely Malaysia, Indonesia, Thailand and Vietnam.